Clima organizacional y satisfacción laboral en la empresa Florícola Ever Green Roses S.A. - Quimbita Rocana, Johana Aradelly (2018)
The objective of this research is to measure the organizational relationship and job satisfaction of the workers of the Ever Green Roses S.A. Flower Company, for which it was necessary to investigate the theoretical foundations related to organizational relationship and job satisfaction in business change. In the theoretical and scientific aspects, the factors that influence the organizational relationship were analyzed, as well as the determination of the job satisfaction that each worker must have within their work area, seeking a good work performance that contributes to the productivity of the Ever Green Roses S.A Flower Company. The methodology of Litwin and Stringer and the (JDI) was applied to determine the correlation between the variables, with the purpose of analyzing the impact of the organizational relationship on the job satisfaction of the Ever Green Roses S.A Flower Company, for the taking of actions of part of management, the methodologies applied through the measurement instruments for our research were: Litwin and Stringer to determine the independent variable organizational relationship, and the (JID) to determine the dependent variable in the labor satisfaction, that will establish the quantitative and qualitative approach, descriptive and exploratory research, with the bibliographic methods to contributed to the recollection of information, it was also necessary to determine the techniques and instruments according to the methodological design of the study. The results obtained through the analysis allowed to know that the Flower Company had no structured human talent management and it was determined that the work environment must be strengthened in order to have the communication of the workers and achieve that the production increase in the company that is why the research lies in the management of the staff and contributes to the efficiency and continuous improvement of the performance of the workers, generating a successful work environment that helps to meet the objectives set by this flower company, in such a way can achieve its business purposes.